Influence application problem-based learning on students' learning outcomes in chemistry at SMA 1 Tanjung Batu - Izzati; Sukaryawan, Made; Lesmini, Bety (Institute for Advanced Science, Social, and Sustainable Future, 2023)
This study aims to determine whether there is an influence of the problem based learning model on the chemistry learning outcomes of SMA Negeri 1 Tanjung Batu. The research method was using a quasi-experimental design with non-equivalent control group design. The sample used was students of class XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class. From the research results obtained, the average prates value in the experimental class is 29.39 and the average pascates is 68.18. While the average prates in the control class is 22.35 and the pascates average is 54.70. The results of the hypothesis test analysis using the t test at a significance level of 5%, obtained t (count) > t (table), that is (2.988)> (1.997). Thus H0 is rejected, meaning that there is an influence of the problem based learning model on the chemistry learning outcomes of the salt hydrolysis material of students in eleventh grade of SMA Negeri 1 Tanjung Batu. It is recommended for teachers to be able to use the problem based learning model as an alternative learning model in an effort to improve student learning outcomes and activeness.